High performance drive circuits for integrated microLED/CMOS arrays for visible light communication (VLC) - Mahmood Zuhdi, Ahmad Wafi; Zuhdi, Ahmad (The University of Edinburgh, 2015)
Wireless communication is a form of communication that has been around for over hundreds of years and is the fastest growing segment of the communication industry. Today, wireless communication has become an essential part of almost everyone’s daily life, and the number of users has increased exponentially over the last decade with the introduction of the internet, mobile devices and smart phones. Radio Frequency (RF) transmission is arguably the most popular method of communication and is available worldwide. With the rapid progress in technology and the increase of number of users, the limited RF spectrum is becoming more congested which led to numerous research efforts to find an alternative that can help to alleviate the pending problem. One of the proposed solutions is Visible Light Communication (VLC), which uses visible Light Emitting Diode (LED) for data transmission. In this thesis, three integrated microLED/Complementary Metal Oxide Semiconductor (CMOS) Integrated Circuits (ICs) are presented with the main aim of increasing the data rate of transmission. The first microLED/CMOS IC presented here is the Generation V microLED/CMOS driver which represents the continuation of the earlier work in the HYPIX project, which aimed to develop a microLED/CMOS driver to optically pump an organic polymer laser. A 40x10 pixelarray of Generation V microLED/CMOS driver was thus designed, primarily for optical pumping polymer lasing purposes, but has also demonstrated the ability to perform communication transmission using an On-Off Keying (OOK) modulation scheme. The driver consumes up to 330mA current and produces approximately 12mW of optical power from a single pixel, which is about 3 times higher than its predecessor. The second microLED/CMOS IC is the microLED/CMOS Current Feedback (CCFBK) driver which was designed to facilitate Orthogonal Frequency Division Multiplexing (OFDM) modulation. OFDM is one of the modulation schemes, adopted from the RF domain, that was proposed to be implemented in VLC in order to increase the data transmission rate. To the best of the author’s knowledge, the microLED/CCFBK driver is the first CMOS driver for microLED that was designed to perform analogue modulation for VLC purposes. The driver is characterised and shows the ability to produce up to 3.5mW of optical power with a data transmission rate of up to 486Mbit/s. The microLED/CMOS Optical Feedback (COFBK) driver is the third microLED/CMOS IC presented in this thesis. The driver looks to improve on the performance of the microLED/CCFBK driver. OFDM transmission requires high linearity to ensure low Bit Error Rate (BER) transmission. However, the optical power output of an LED is not, in general, linear with the input voltage signal. The microLED/COFBK driver looks to increase the linearity of the optical power output by integrating a microLED and a photodiode in a single pixel to create a feedback loop. Once again, to the best of the author’s knowledge, the microLED/COFBK driver is the first CMOS driver for microLED which integrates both optical source and sensor in a single pixel to help linearise the optical power output for communication purposes; in this case, VLC. For a similar range of optical power, the microLED/COFBK driver shows a reduction about 5.3% in the degree of non-linearity compared to the microLED/CCFBK driver and produces lower Total Harmonic Distortion (THD). The microLED/COFBK driver showed the potential to increase the data rate by a factor of four over that of microLED/CCFBK driver. The analogue modulated microLED/CMOS ICs described here are the first-generation drivers that have demonstrated the possibilities to increase the data rate using OFDM. A number of possible design improvements have been identified which will enhance future performance and integration with the standard VLC system.
Keywords: Visible Light Communication; VLC